Comparison of IncK-blaCMY-2 Plasmids in Extended-Spectrum Cephalosporin-Resistant Escherichia coli Isolated from Poultry and Humans in Denmark, Finland, and Germany - Meiyao Che; Ana Herrero Fresno; Cristina Calvo-Fernandez; Henrik Hasman; Paula E. Kurittu; Annamari Heikinheimo; Lisbeth Truelstrup Hansen (MDPI AG, 2024)
Escherichia coli carrying IncK-blaCMY-2 plasmids mediating resistance to extended-spectrum cephalosporins (ESC) has been frequently described in food-producing animals and in humans. This study aimed to characterize IncK-blaCMY-2-positive ESC-resistant E. coli isolates from poultry production systems in Denmark, Finland, and Germany, as well as from Danish human blood infections, and further compare their plasmids. Whole-genome sequencing (Illumina) of all isolates (n = 46) confirmed the presence of the blaCMY-2 gene. Minimum inhibitory concentration (MIC) testing revealed a resistant phenotype to cefotaxime as well as resistance to ≥3 antibiotic classes. Conjugative transfer of the blaCMY-2 gene confirmed the resistance being on mobile plasmids. Pangenome analysis showed only one-third of the genes being in the core with the remainder being in the large accessory gene pool. Single nucleotide polymorphism (SNP) analysis on sequence type (ST) 429 and 1286 isolates showed between 0-60 and 13-90 SNP differences, respectively, indicating vertical transmission of closely related clones in the poultry production, including among Danish, Finnish, and German ST429 isolates. A comparison of 22 ST429 isolates from this study with 80 ST429 isolates in Enterobase revealed the widespread geographical occurrence of related isolates associated with poultry production. Long-read sequencing of a representative subset of isolates (n = 28) allowed further characterization and comparison of the IncK-blaCMY-2 plasmids with publicly available plasmid sequences. This analysis revealed the presence of highly similar plasmids in ESC-resistant E. coli from Denmark, Finland, and Germany pointing to the existence of common sources. Moreover, the analysis presented evidence of global plasmid transmission and evolution. Lastly, our results indicate that IncK-blaCMY-2 plasmids and their carriers had been circulating in the Danish production chain with an associated risk of spreading to humans, as exemplified by the similarity of the clinical ST429 isolate to poultry isolates. Its persistence may be driven by co-selection since most IncK-blaCMY-2 plasmids harbor resistance factors to drugs used in veterinary medicine.